Packaging Design and Marketing of Online Seaweed Products in Aeng Dake Village, Bluto District, Sumenep Regency - Annur Ahadi Abdillah; Eka Saputra; Adriana Monica Sahidu; Dwi Yuli Pujiastuti (Journal of Marine and Coastal Science, 2018)
Online marketing training is given to the fishermen groups of Karang Baru and Fisheries Vocational School Nasyrul Ulum Aeng Dake covering about the theory of marketing concepts, use of Web media and social media and online marketing-based governance. Community service is expected to be able to provide the ability of the community to package products into attractive packaging and the community can use marketing online so as to expand the reach of marketing, namely reaching regional and national areas. With the community service, it is expected to increase the economy of the seaweed grass cultivation community in Aeng Dake Subdistrict Seaweed Village. Community service activities are carried out by various methods, namely theoretical and practical training and assistance in online marketing media management activities. and practices aimed at students of the Nasyul Ulum Aeng Dake Vocational School of Fisheries Products Processing. The training provided was in the form of introducing various kinds of interesting packaging forms. The training activities continued on the direct practice of product packaging as well as presentations from student students regarding packaged products. The activity aimed at the Karang Baru fishermen group is in the form of assistance in making online marketing media, namely web and social media.